MAKING THE CURRICULUM INCLUSIVE IN TWO EUROPEAN UNIVERSITIES: APPROACHES, CHALLENGES AND OPPORTUNITIES - Garcia Iriarte, Edurne (Padova University Press, 2025)
International policy developments and an incipient scholarship on equality, diversity and inclusion (EDI) (Crimmins, Cyr) provide both direction and theoretical justification towards inclusive higher education. As the European higher education student population is increasingly more diverse (Hauschildt et al.), an inclusive curriculum recognises and responds to the different ways in which students engage, access and are represented in the curriculum (Buitendijk et al.). Inclusive curriculum has been defined as “curriculum which takes into consideration and caters for the diverse needs, previous experiences, interests and personal characteristics of all learners. It attempts to ensure that all students are part of the shared learning experiences of the classroom and that equal opportunities are provided, regardless of learner differences” (UNESCO International Bureau of Education)
Why EDI Matters Equ(al)ity, Diversity and Inclusion in European Universities
PUBLISHED
Padova
Keywords: Inclusive Society